2011
DOI: 10.1186/1471-2253-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia and postoperative analgesia with ropivacaine and fentanyl in off-pump coronary artery bypass grafting: a randomized, controlled study

Abstract: BackgroundOur aim was to assess the efficacy of thoracic epidural anesthesia (EA) followed by postoperative epidural infusion (EI) and patient-controlled epidural analgesia (PCEA) with ropivacaine/fentanyl in off-pump coronary artery bypass grafting (OPCAB).MethodsIn a prospective study, 93 patients were scheduled for OPCAB under propofol/fentanyl anesthesia and randomized to three postoperative analgesia regimens aiming at a visual analog scale (VAS) score < 30 mm at rest. The control group (n = 31) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…On the other hand, studies have shown that 30% of hernia in propofol anesthesia improves hemodynamic stability by reducing the patient's norepinephrine requirement [ 27 ]. Of course, some new anesthesia methods are now available, such as remifentanil target-controlled infusion, constant-rate infusion, chest epidural anesthesia (EA), and postoperative epidural infusion (EI) [ 28 , 29 ]. During the operation, drugs are often used, so we analysed the potential drugs of the two anesthesia methods to provide guidance for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that 30% of hernia in propofol anesthesia improves hemodynamic stability by reducing the patient's norepinephrine requirement [ 27 ]. Of course, some new anesthesia methods are now available, such as remifentanil target-controlled infusion, constant-rate infusion, chest epidural anesthesia (EA), and postoperative epidural infusion (EI) [ 28 , 29 ]. During the operation, drugs are often used, so we analysed the potential drugs of the two anesthesia methods to provide guidance for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Патогенез респираторных осложнений при коронарном шунтировании связан с хирургической травмой, искусственным кровообращением, гемотрансфузией, избыточным гидробалансом, неадекватным купированием болевого синдрома, ателектазированием легких и другими факторами [45,47]. Высокая торакальная эпидуральная анестезия в кардиохирургии за счет купирования болевого синдрома, десимпатизации, снижения давления и перераспределения жидкости в малом круге кровообращения может способствовать уменьшению выраженности отека и ателектазирования легких, а также снижению частоты дыхательных осложнений [48][49][50][51][52][53][54].…”
Section: эпидуральная анестезия и послеоперационные дыхательные осложненияunclassified
“…Такой подход укорачивает время нахождения в отде-лении интенсивной терапии и снижает экономические издержки [79]. Эпидуральное введение местных анестетиков обеспечивает повышение качества анальгезии в периоперационном периоде АКШ, что подтверждается целым рядом исследований [53,80,81]. Кроме того, проведение эпидуральной анальгезии при коронарном шунтировании способствует улучшению артериальной оксигенации и уменьшает длительность искусственной вентиляции легких [50,53,82].…”
Section: эпидуральная анестезия как компонент мультимодальной анальгезии и ранней активизации после кардиохирургических вмешательствunclassified
See 1 more Smart Citation
“…Changes in magnesium levels can cause abnormal blood coagulation, leading to bleeding complications after OPCABG [ 14 ]. In OPCABG, ropivacaine and fentanyl can be used to temporarily reduce arterial pressure, optimize myocardial function, and affect perioperative fluid and vasoactive treatment [ 15 ]. Recent studies have shown that dexmedetomidine, as an effective adjuvant, can reduce hospital stays in patients receiving OPCABG [ 16 ].…”
Section: Introductionmentioning
confidence: 99%